The Usborne children's encyclopedia - Craig, Annabel; Crawford, Susan; Elliott, Jane.; King, Colin (London ; Tulsa, Okla. : Usborne/EDC, 1987)
Arranged thematically, providing simple explanations of everyday things and key concepts.
4.0
3-6
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; Encyclopedias and dictionaries